Pan-neutralizing, germline-encoded antibodies against SARS-CoV-2: Addressing the long-term problem of escape variants - Lunderberg, Justin Mark; Dutta, Sanjucta; Collier, Ai-Ris Y.; Lee, Jeng-Shin; Hsu, Yen-Ming; Wang, Qiao; Zheng, Weina; Hao, Shushun; Zhang, Haohai; Feng, Lili; Robson, Simon C.; Gao, Wenda; et al. (Frontiers in Immunology, 2022)
Despite the initially reported high efficacy of vaccines directed against ancestral SARS-CoV-2, repeated infections in both unvaccinated and vaccinated populations remain a major global health challenge. Because of mutation-mediated immune escape by variants-of-concern (VOC), approved neutralizing antibodies (neutAbs) effective against the original strains have been rendered non-protective. Identification and characterization of mutation-independent pan-neutralizing antibody responses are therefore essential for controlling the pandemic. Here, we characterize and discuss the origins of SARS-CoV-2 neutAbs, arising from either natural infection or following vaccination. In our study, neutAbs in COVID-19 patients were detected using the combination of two lateral flow immunoassay (LFIA) tests, corroborated by plaque reduction neutralization testing (PRNT). A point-of-care neutAb LFIA, NeutraXpress™, was validated using serum samples from historical pre-COVID-19 negative controls, patients infected with other respiratory pathogens, and PCR-confirmed COVID-19 patients. Surprisingly, potent neutAb activity was mainly noted in patients generating both IgM and IgG against the Spike receptor-binding domain (RBD), in contrast to samples possessing anti-RBD IgG alone. We propose that low-affinity, high-avidity, germline-encoded natural IgM and subsequent generation of class-switched IgG may have an underappreciated role in cross-protection, potentially offsetting immune escape by SARS-CoV-2 variants. We suggest Reverse Vaccinology 3.0 to further exploit this innate-like defense mechanism. Our proposition has potential implications for immunogen design, and provides strategies to elicit pan-neutAbs from natural B1-like cells. Refinements in future immunization protocols might further boost long-term cross-protection, even at the mucosal level, against clinical manifestations of COVID-19.